Importance, Novelty and Formulation of Indian Weathering Cycle - Shamasundara, B V; Shridhar, Dr. T N; Krishna, Dr. S A Mohan (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
Weathering is the adverse response of a material or product to climate, often causing unwanted and premature product failure. The factors responsible for weathering are; solar radiation (light energy), temperature and water (moisture). The specifications of weathering cycles in Indian standards refereed from European regulations, American standards or Japanese standards; hence the entire weathering specifications based on the respective countries data. These specifications may not be suitable for Indian weathering climate as well as usage requirements. Any material design should permit the independent selection of the major degrading forces such as UV radiation, temperature, humidity, and rain. Thus the selection of the right combination for a particular location and time of year should be easy and should give a cycle that truly simulates natural conditions. Hence, deriving the data for the standards as per Indian requirements is of prime importance. In this context, collected the Indian climatic data from five different regions considering India is one of the largest geographical areas and standardize India specific weathering test specification/ cycle. Daily solar radiation (light energy), temperature, humidity and rainfall data collected from metrology department of different regions of India for the period 5 years are used to study the climatology and spatial and temporal characteristics of Indian weathering variations. Comparison of the Indian wreathing data with the Global weathering cycle shows a variation in each parameters. The India specific weathering data collected during the course of this study will prove to be of significant importance to automobile manufacturers, testing agency and useful in development of Indian weathering standards. Also India specific weathering study of polymers helps Indian automobile manufacturer for selection of polymers as per Indian conditions.